Paleomagnetism and rock magnetism of the ca. 1.87 Ga Pearson Formation, Northwest Territories, Canada: A test of vertical-axis rotation within the Great Slave basin - Gong, Z.; Xu, X.; Evans, D.; Hoffman, P.; Mitchell, Ross; Bleeker, W. (Elsevier BV, 2018)
A geometrically quantitative plate-kinematic model, based on paleomagnetism, for the initial assembly of Laurentia has taken form in the past few decades. Within this framework, there remains but one problematic interval of data predominantly from the Slave craton, which is the 1.96–1.87 Ga Coronation apparent polar wander path (APWP). The Coronation APWP shows large (~110°) back-and-forth oscillations that are difficult to explain in terms of plate motion. Nonetheless, poles from the Coronation APWP have been incorporated in various paleogeographic reconstructions of Laurentia and the supercontinent Nuna, pointing to the importance of testing its veracity. In this study, we conducted a detailed paleomagnetic and rock magnetic study of the ca. 1.87 Ga Pearson Formation, East Arm of Great Slave Lake, Northwest Territories, Canada. Our results show that Pearson Formation yields a characteristic remanent magnetization carried by single-domain or small pseudo-single-domain magnetite. The age of the magnetization is constrained to be older than Paleoproterozoic deformation and is interpreted as primary. Paleomagnetic declinations reveal a one-to-one correlation with local structural attitudes, indicating that some small blocks in the fold belt likely experienced significant (~60°) vertical-axis rotations, presumably related to large dextral displacements along the McDonald Fault system. Alternative explanations, such as true polar wander or a non-dipole magnetic field, are considered less parsimonious for the data presented here. It is suspected that some existing Christie Bay Group poles (the Stark and Tochatwi Formations), which were sampled in areas with anomalous structural attitudes and differ from time-equivalent poles obtained from areas of the Slave craton far from major transcurrent faults, may similarly suffer from vertical-axis rotation. We suggest further study before using possibly rotated Christie Bay Group poles for paleogeographic reconstructions.